Proteína SOFT na formação de CATs em espécies de Colletotrichum do feijoeiro - Mota, Suellen Finamor (2017)
Anthracnose of common bean is caused by Colletotrichum lindemuthianum fungi. However, Glomerella sp., no pathogenic strains have been isolated from anthracnose lesions and do not correspond to sexual form of C. lindemuthianum. These species form conidial anastomosis tubes (CATs), which are specialized structures that emerge as protuberances of conidia afte r or during germination, depending on species. CATs fusion allows communication between cytoplasm of two or more conidia and organelles transference can occur, such as mitochondria and nuclei. Two proteins, SOFT (SO) and MAK-2, are responsible for conidia communication and CATs fusion in Neurospora crassa. However, there is no information about these proteins in C. lindemuthianum. Objective of this study was to characterize CATs formation in these species, localize, sequence and express the clsoft and glsoft (clso and glso) gene, study the CLSO and GLSO protein during CATs formation, and also to observe the effects of silenced gene, mainly in pathogenicity. In addition, to observe CATs occurrence among species/strains studied. The LV134 strain of C. lindemuthianum, race 65 and G7-2 strain of Glomerella sp. were used. clso and glso gene were isolated, sequenced and strains were transformed with so gene linked with GFP protein. These gene were also silenced by yeast cloning and recombination technique. All wild type and transformed strains of both species were characterized for Index of mycelial growth rate, colonial diameter, sporulation rate, germination percentage and pathogenicity test. Both species were uninucleated before and after spore germination. Strains presented mycelial and sexual incompatibility, however, there were CATs formation between and within evaluated species. In addition, no specificity occurred in the choice of fusion partner. It was also observed that the best temperature for CATs formation was 20°C. CLSO and GLSO protein presented oscillatory recruitment and were essential in CATs formation in C. lindemuthianum and Glomerella sp. Species, respectively. CLSO and GLSO protein did not present a pleiotropic effect for evaluated traits. Results suggest that CATs formation may be contributing to variability increase and emergence of new Colletotrichum species in common bean.